2012
DOI: 10.1371/journal.pone.0032445
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bone and Renal Effects In HIV-infected Adults Switching to Abacavir or Tenofovir Based Therapy in a Randomized Trial

Abstract: IntroductionOur objective was to compare the bone and renal effects among HIV-infected patients randomized to abacavir or tenofovir-based combination anti-retroviral therapy.MethodsIn an open-label randomized trial, HIV-infected patients were randomized to switch from zidovudine/lamivudine (AZT/3TC) to abacavir/lamivudine (ABC/3TC) or tenofovir/emtricitabine (TDF/FTC). We measured bone mass density (BMD) and bone turnover biomarkers (osteocalcin, osteocalcin, procollagen type 1 N-terminal propeptide (P1NP), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 39 publications
7
43
1
Order By: Relevance
“…New markers of tubular dysfunction, such as neutrophil gelatinase-associated lipocalin (NGAL), may be used to evaluate kidney damage during TDF therapy (40)(41)(42). In the past, various studies have been published demonstrating the usefulness of NGAL as an early biomarker of tubular damage in HIV-infected patients treated with TDF (43)(44)(45)(46). Conversely, the body of evidence in HBV patients, at present, is equivocal.…”
Section: Dose Adjustment Of Tdf and Early Diagnosis Of Tdf-related Rementioning
confidence: 99%
“…New markers of tubular dysfunction, such as neutrophil gelatinase-associated lipocalin (NGAL), may be used to evaluate kidney damage during TDF therapy (40)(41)(42). In the past, various studies have been published demonstrating the usefulness of NGAL as an early biomarker of tubular damage in HIV-infected patients treated with TDF (43)(44)(45)(46). Conversely, the body of evidence in HBV patients, at present, is equivocal.…”
Section: Dose Adjustment Of Tdf and Early Diagnosis Of Tdf-related Rementioning
confidence: 99%
“…However, TDF is currently the antiretroviral drug most associated with BMD loss. [37,42,43]. Results from several randomized clinical trials among antiretroviral naive patients have shown that initiation of cART is associated with a decrease in bone mineral density (BMD) of 2%-6% at both the hip and the spine, which occurs within the first year of treatment, with stabilization thereafter [40,[43][44][45][46][47][48][49].…”
Section: Toxicity Issuesmentioning
confidence: 99%
“…Results from several randomized clinical trials among antiretroviral naive patients have shown that initiation of cART is associated with a decrease in bone mineral density (BMD) of 2%-6% at both the hip and the spine, which occurs within the first year of treatment, with stabilization thereafter [40,[43][44][45][46][47][48][49]. Three trials directly compared TDF/FTC with ABC/3TC and found greater decreases in BMD with TDF/FTC-based treatment [40,43,48]. Also, in a randomized clinical trial with patients with osteoporosis or osteopaenia, switching from TDF to ABC was followed by an increase of BMD in femur but not in spine [1,37].…”
Section: Toxicity Issuesmentioning
confidence: 99%
“…Multiple randomized ART trials have documented significantly greater bone loss in patients initiating, or switching to, a tenofovir disoproxil fumarate (tenofovir DF)-containing ART regimen [30][31][32][33][34][35][36] compared with abacavir-containing regimens. In those with low BMD, switching from tenofovir DF to a raltegravir-containing regimen was associated with an increase in BMD [37].…”
Section: Art and Bone Massmentioning
confidence: 99%